2021
DOI: 10.3389/fped.2021.681626
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Obesity—A Potential Risk Factor for Systemic Inflammatory Syndrome Associated to COVID-19, a Case Report

Abstract: The well-documented systemic inflammation associated to pediatric obesity might act as an augmenting factor for other inflammatory conditions, such as pediatric inflammatory multisystem syndrome (PIMS) associated to COVID-19. We report the case of 9-year-old boy admitted in our clinic for fever, anorexia, and fatigability. The clinical exam revealed influenced general status, palpebral edema, non-exudative conjunctivitis, and abdominal tenderness. The patient weighed 45 kg. The laboratory tests at the time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 29 publications
(39 reference statements)
2
19
0
Order By: Relevance
“… 60 , 61 Higher leptin levels have been demonstrated in SARS‐CoV‐2 ventilated patients and positively associated with high BMI. 62 During these past 2 years, several other inflammation biomarkers, including CRP, 26 , 27 , 28 , 29 , 31 , 32 , 35 , 37 , 40 , 41 , 44 , 63 innate receptors, 52 , 64 complement, 47 , 65 and lipidic mediators 47 have been associated with COVID‐19 severity in patients with obesity (Table 3 , Figures 2 and 3 ).…”
Section: Resultsmentioning
confidence: 99%
“… 60 , 61 Higher leptin levels have been demonstrated in SARS‐CoV‐2 ventilated patients and positively associated with high BMI. 62 During these past 2 years, several other inflammation biomarkers, including CRP, 26 , 27 , 28 , 29 , 31 , 32 , 35 , 37 , 40 , 41 , 44 , 63 innate receptors, 52 , 64 complement, 47 , 65 and lipidic mediators 47 have been associated with COVID‐19 severity in patients with obesity (Table 3 , Figures 2 and 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…21 Among MIS-C cases, obesity was the most common comorbidity, consistent with the report of Hoste, et al 16 With obesity being associated with a chronic subclinical inflammatory status, it is hypothesized that COVID-19 infection triggers a greater hyperinflammatory response and higher endothelial, macrophage and adipocyte activation, leading to considerably elevated inflammatory markers and more severe complications. 22,23 Fever, cough, and colds were the predominant symptoms. However, gastrointestinal symptoms were also commonly reported, similar to those of Lu, et al 12 Inflammatory markers (CRP, procalcitonin and D-dimer) and markers for organ dysfunction (AST, ALT and LDH) were significantly higher in severe and critical disease compared to non-severe disease, similar to the study of Martin, et al 13 Radiographic findings were mostly normal, as reported in other studies.…”
Section: Resultsmentioning
confidence: 99%
“…Although without statistical significance, our study also indicated the male gender to be more frequently diagnosed with PIMS, and the mean age of PIMS children was also above the age of 6 years. Unfortunately, the symptoms of both COVID-19 and PIMS frequently overlap, especially in terms of gastrointestinal symptoms and fever [ 22 , 23 ]. In fact, fever is a mandatory symptom according to the diagnostic criteria of PIMS, but it seems that only half of COVID-19 children develop fever [ 8 , 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%